Use of the counter selectable marker PheS for genome engineering in Staphylococcus aureus - Schuster,C; Howard,S; Grundling,A (Microbiology, 2019)
The gold standard tocreate gene deletions in Staphylococcus aureusis by homologous 16recombination using allelic exchange plasmids with a temperature sensitive origin of replication. A knockout vectorthat containsregions of homologyis first integrated into thechromosome of S. aureus by a single crossover event selected for at high temperatures (non-permissive for plasmid replication) and antibiotic selection. Next, the second crossover event is encouraged by 20growth without antibiotic selection at lowtemperature, leading at a certain frequencyto the excision of the plasmid and deletionof the gene of interest.To detector encourage plasmid loss, either a beta-galactosidase screening method or more typically, a counter selection step is used. We here present the adaption of the counter selectable markerpheS, coding for a mutated subunit of the phenylalanine-tRNA-synthetase for use in S. aureus. The PheS protein variant allows for the incorporation of the toxic phenylalanine amino acid analoguepara-chlorophenylalanine(PCPA)into proteins and the addition of 20-40 m M PCPAto rich medialeads to a drasticgrowth reductionof S. aureus and supplementing chemically defined medium with 2.5-5 mM PCPA to a complete growth inhibition. Using the new allelic exchange plasmid pIMAY, wedeletedthe magnesium transporter gene mgtEin S. aureusUSA300 LAC(SAUSA300_0910/ SAUSA300_RS04895) and RN4220(SAOUHSC_00945) and demonstrate that cobalt toxicity in S. aureusis mainly mediated by the presence of MgtE.This new plasmid will aidto efficiently and easily create gene knockouts in S. aureus.